Environmental Friendly Residential Villa - Ahmad Jarrar; Mohammad Qassem Suliman; Nehad Rabayaa (My University, 2015)
Traditional energy source (petroleum , .gas , ..ets )  will not enough in future to secure human demands. Now a day , the world were interested to energy benefit from renewable energy sources like the sun and wind due to their  availability. From this point the Environmental Friendly  building  has become the most important topic for Engineering to provide comfort and cost efficiency for humans . The Importance of this project is to create a comfortable living environmental for people and  to reduce the negative  impacts of such buildings on the environmental by reducing energy consumption , the proper use of renewable energy will contribute in reducing pollution improving the quality of life for the community  .

Traditional energy source (petroleum , .gas , ..ets )  will not enough in future to secure human demands. Now a day , the world were interested to energy benefit from renewable energy sources like the sun and wind due to their  availability. From this point the Environmental Friendly  building  has become the most important topic for Engineering to provide comfort and cost efficiency for humans . The Importance of this project is to create a comfortable living environmental for people and  to reduce the negative  impacts of such buildings on the environmental by reducing energy consumption , the proper use of renewable energy will contribute in reducing pollution improving the quality of life for the community  .
Environmental Friendly Residential Villa